PD-L1 expression in large cell neuroendocrine carcinoma of the lung. (April 2018) - Eichhorn, F.; Harms, A.; Warth, A.; Muley, T.; Winter, H.; Eichhorn, M.E.
Highlights: LCNEC is rare and associated with poor prognosis. The prognostic implication of the PD1/PD-L1 pathway in LCNEC is unknown. PD-L1 expression on LCNEC was connected with poorer outcome. PD-L1 exclusively in the tumor microenvironment was associated with better survival. Abstract: Objectives: Large cell neuroendocrine carcinoma of the lung (LCNEC) is associated with an unfavorable prognosis and only few patients are eligible for surgery. In most patients, chemotherapy is recommended alone or in addition to resection. Novel immunotherapies blocking the PD-L1 pathway have been introduced into therapeutic regimens for NSCLC with great success. In order to evaluate a possible efficacy of an anti-PD-L1 therapy, we analyzed the frequency of PD-L1 expression in LCNEC. Material and methods: We retrospectively reviewed data from 76 patients with LCNEC treated in our institution between 1998 and 2010. The expression of PD-L1 was examined on the tumor cells and the tumor surrounding tissue by immunohistochemistry. An expression of >1% was considered as positive. Statistical analysis was performed to determine significant predictors for survival. Results: 56 of 76 patients with LCNEC were treated with a potentially therapeutic surgical approach. Tumor-specific survival (TSS) of the entire cohort was 29% at five years. 17 patients (22.3%) had PD-L1 positive tumors and 12 of these had no additional PD-L1 expression in the adjacent immune cell infiltrate. Tumor-flanking immune cells were found PD-L1 positive 28 patients; 16 of these had no additional expression on the tumor cells. The most considerable difference in survival was found when comparing patients with isolated PD-L1 expression on tumor cells and PD-L1 negative immune cell infiltrate to their counterpart (positive immune-cell infiltrate and PD-L1 negative tumor cell surface; 5-year TSS: 0% vs. 60%; p < 0.017). Conclusion: PD-L1 expression in LCNEC was associated with poorer survival whereas PD-L1 expression in the tumor microenvironment seemed to have a beneficial effect. Therapeutic approaches have to be evaluated in future.